La doble marginalidad de José de Acosta: religión y soberanía en el virreinato del Perú (siglo XVI) - Vigneron de La Jousselandière, Victor Santos (2012)
With this article we seek to reflect on the status conferred on the European extra alterity in the work of the Jesuit José de Acosta. On the one hand, such an analysis can highlight some uses of religion as a tool for understanding the barbarian populations; onthe other hand, it is about showing the nexus between the evangelizing project and the institution of a form of Spanish sovereignty over the viceroyalty of Peru, in the second half of the sixteenth century